Health Sciences Faculty’s Perceptions of Educational Changes During COVID-19: Global Lessons - Karima Lalani; Tanya E. Karwaki; James Condon (Trends in Higher Education)
The COVID-19 pandemic had a significant impact on health sciences education, and impacted clinical training, teaching methodologies, and institutional practices. Within the higher education literature during the height of the pandemic, several research studies focused on the impact of the pandemic on the students, but not on health sciences educators. Our study used thematic analysis to analyze the higher education literature from the CHELD v2 database to learn about the perspectives of health sciences educators. Out of 738 articles in the CHELD v2 database, we identified 14 articles that were focused on the perspectives of health sciences educators. The resulting thematic categories related to faculty development, student assessment, clinical education techniques, and insights into the pivot to online teaching. While our study contributes to the health sciences education literature by identifying themes from global health sciences educators’ perspectives, this study also paves the way to better understand institutional and student perspectives in a more inclusive way for the health sciences.